Correlation Between Flying Insect Diversity and Environmental Factors in Various Land Use Types in Paseh District, Sumedang Regency, West Java - Susanti Withaningsih; Bilhaq Fahmi Ilmi; Parikesit Parikesit (Diversity)
Indonesia is known for its incredible diversity of insects. Being ectothermic, insects are influenced by environmental factors. The relationship between insect diversity and the environment can be understood using multivariate analysis. The Paseh District in Sumedang Regency has various land uses, including gardens, rice fields, and plantations. Changes in land use due to the construction of the Cisumdawu Toll Road can impact environmental factors, such as soil quality, microclimate, and water availability, which are critical for sustaining diverse insect communities. Similarly, changes in vegetation cover can alter temperature and humidity levels, impacting terrestrial insects adapted to specific climatic conditions. This study aims to gather information on the relationship between insect diversity and environmental factors in different land use types in the Paseh District. A preliminary survey was carried out to record land use types and determine sampling locations. An intensive survey was done to collect and identify flying insect samples, as well as to measure the environmental factors. The results were analyzed using the Shannon–Wiener Diversity Index (H’), Evenness Index (E’), Simpson’s Diversity Index (C), and Canonical Correspondence Analysis (CCA). The study found 115 species of flying insects, with mixed gardens having the highest diversity. The CCA results showed that temperature strongly and positively correlated with insect diversity across all land uses, while wind speed correlated positively with insect diversity in gardens. Altitude correlated negatively with insect diversity in mixed gardens but positively in rice fields. Humidity had a strong positive correlation with insect diversity in other land uses. This research is important for understanding how land use types and environmental factors influence flying insect diversity, which is crucial for conserving biodiversity and maintaining essential ecosystem services such as pollination and pest control. Its impact lies in providing scientific data to guide sustainable land management practices, support agricultural productivity, and inform policies for biodiversity conservation in the Paseh District and similar regions.